PENERAPAN GREEN BUILDING SEBAGAI PENCAPAIAN SUSTAINABLE ARCHITECTURE PADA PASAR BADUNG BALI - Zoya Natalia (Universitas Trisakti, 2019)
AbstractEnvironmental issues, especially global warming are being hangat-hangatnya talked about in the world.is in the world of architecture emerging health problems and inconvenience because of air quality andair pollution in occupied buildings that affect the productivity of the occupants, the presence of poorair ventilation, and less natural lighting. This is due to several things, for example: Ozone emissionphotocopier, Pollutants from wood furniture and panels, cigarette smoke, etc... The creation or innovationof renewable energy has also become the backdrop of green architecture concept. Green Building CouncilIndonesia (GBCI) is a green building certification provider in Indonesia based on a typical Indonesianassessment device called Greenship Similarly, the development of the parent market, post-fire marketrenovation and other market development will seek to construct the implementation of green building/green design, which is efficient in the use of resources and reduction of greenhouse gas emissions. Theproblem that will be discussed is whether the Pasar Badung has applied the concept of green buildingas the achievement of sustainable architecture? The research methods used are research based on thestudy of literature both printed and electronic and direct observation (observation). Fresh air circulationcan easily enter every room of the building. Natural lighting from the sunlight can also illuminate intoevery room well and feel comfortable. The Material used is the raw acian floor, the raw plastering wallis painted. For waste disposal is available for three types of plastic waste, metal and organic.Keyword: green design, green building, sustainable architecture, pasar Badung AbstrakPermasalahan lingkungan khususnya pemanasan global sedang hangat-hangatnyadibicarakan dalam dunia arsitektur muncul permasalahan kesehatan dan ketidak nyamanankarena kualitas udara dan polusi udara dalam bangunan yang ditempati yang mempengaruhiproduktivitas penghuni, ventilasi udara yang buruk, dan kurangnya pencahayaan alami. Halini disebabkan oleh beberapa hal, misalnya: emisi ozon mesin fotocopy, polusi dari perabotdan panel kayu, asap rokok, dsb.. Penciptaan atau inovasi energi yang terbarukan juga menjadilatar belakang timbulnya konsep green architecture. Green Building Council Indonesia (GBCI)adalah pemberi sertifikasi bangunan hijau di Indonesia berdasarkan perangkat penilaian khasIndonesia yang disebut Greenship demikian halnya pembangunan pasar induk, renovasi pasarpaska kebakaran dan pembangunan pasar lainnya akan mengupayakan pembinaan terhadapimplementasi bangunan Gedung hijau/ green design, yang efisien dalam penggunaan sumberdaya maupun pengurangan emisi gas rumah kaca. Permasalahan yang akan dibahas adalahapakah Pasar Badung sudah menerapkan konsep green building sebagai pencapaian sustainablearchitecture? Metode penelitian yang digunakan adalah penelitian yang didasarkan pada studiliteratur baik tercetak maupun elektronik dan pengamatan (observasi) langsung. Sirkulasiudara segar dapat dengan mudah masuk kesetiap ruangan bangunan. Pencahayaan alami darisinar matahari pun dapat menyinari kedalam setiap ruangan dengan baik dan terasa nyaman.Material yang digunakan adalah lantai acian mentah, tembok plesteran mentah dicat. Untukpembuangan sampahnya tersedia untuk tiga jenis sampah plastik, logam dan organik.Kata kunci: green design, green building, sustainable architecture, pasar Badung